CUSTOMER DECISION MAKING IN SELECTING CINEMA USING ANALYTICAL HIERARCHY PROCESS (AHP) METHOD (CASE STUDY : MANTOS 21, MEGAMALL XXI, CINEMAXX) - Lasut, Falincia Fira; Tumewu, Ferdinand (Sam Ratulangi University, 2015)
ABSTRACT Cinema is not only a place for watching, but that also a place for consumers to accomplish their hobby. Customer decision making is the process of making purchase decisions based on cognitive and emotional influences such as impulse, family, friends, advertisers, role models, moods, and situations that influence a purchase. It is important because in understandingÂ customer decision making, we will understand how consumer make the purchase decision, how the process of decision making by customer from searching until selecting the product or service, and also we can know the factors that influence the decision making. This research used quantitative method. Quantitative research seeks to quantify the data. The method used in this research is Analytical Hierarchy Process (AHP). AHP is a method for ranking decision alternatives and selecting the best one given multiple criteria. It allows users to assess the relative weight of multiple criteria or multiple options against given criteria in an intuitive manner. Keywords : Customer Decision Making, AHP (Analytical Hierarchy Process)